Theological education and theological enlightenment in modern Russia: Conceptualisation, orientation and development prospects - I. Ya. Murzina; N. A. Simbirtseva (Russian State Vocational Pedagogical University, 2022)
Introduction. The discussions in the scientific and educational environment on the scientific status of theology, its prospects in the system of university education, the opportunities opening for religious education in Russia, show the relevance of the analysis of the place of theology as a sphere of scientific knowledge in a number of social and humanitarian sciences and reflections on the essence of theological education and enlightenment that influence the axiological basis of society.Aim. The aim of the study is to conceptualise "theological education" and "theological enlightenment", which define the focus of the conversation about religion today. The objectives of the study are related to determining the scope of each of the concepts and considering promising educational and enlightening practices in Russia.Methodology and research methods. The scientific argumentation presented in the article is based on the following theoretical research methods: logical analysis, structural and functional method, discursive analysis, axiological approach. The basis is an interdisciplinary methodology that allows synthesising approaches peculiar to various social and humanitarian sciences. When describing educational practices, the methods of comparative analysis, systematization and classification were applied.Results. It is determined that the educational paradigm is being changed today: the "return" of the religious component to education is considered as an attempt to set a new education coordinate system in the unity of horizontal (institutional) and vertical (meaning-forming) vectors. The authors define the essence of theological education in a broad (the formation of an axiological basis) and narrow (the process and result of the implementation of values in educational practice) sense. Moreover, the authors reveal the specifics of theological education in professional and comprehensive education. Changes in educational practices over the past few decades have affected educational activities in the field of religion, which required an analysis of the "theological education" concept and the definition of its prospects in a digital society. The authors describe the principles, conditions and directions of the implementation of theological enlightenment.Scientific novelty. The paper presents a terminological analysis of the categories of "theological education" and "theological enlightenment", which are relatively new for pedagogical science.Practical significance. The conclusions presented in the study on the possibilities of theological education and theological enlightenment may be of interest to developers and organisers of religious educational programmes.